TAFSIR AYAT PRODUKSI DALAM EKONOMI SYARIAH - Syifaun Nada (LPPM STAI DARUSSALAM LAMPUNG, 2017)
Production is very principle for the survival and also human and earth civilization. Indeed production is born and grows from the union of humans with nature. Production activities are a chain of consumption and distribution. Production activities that produce goods and services, then consumed by consumers. Without production, economic activity will stop, and vice versa. To produce goods and services, production activities involve many factors of production. One definition of production is the activity of creating benefits in the present and future. Besides the above understanding, the definition of production also refers to the process that transforms input into output. All types of inputs that enter the production process to produce production output are called production factors. Production not only physically creates something that does not exist, but makes something from the old elements of nature useful. From livestock, for example, people can take their skin to make clothes and other finished goods, from milk to livestock can be squeezed into drinks of fresh milk or milk powder for babies. Humans must optimize their minds and expertise to develop investment resources and types of businesses in carrying out what they have said.